(untitled) (Revista de Investigaciones Universidad del Quindío, 2012)
The youth’s group and they meet with base in concrete objectives, when it is to express solidarity and he/she witnesses before the vulneration of the rights of the other ones. It is there where it is evidenced the social capital and their possibilities to contribute to bolster projects and to help to the society in their search of more justness and social justice. With the result that Fukuyama in their book, the great rupture (1999), outline that “the ethical values open step to the social capital”; since starting from the deepest relationships, these associations generate gain, not alone for a person, but for a group or a community